High-yield grass Pennisetum sinese Roxb plantation and organic manure alter bacterial and fungal communities structure in an ecological agriculture farm - He, Yan (AMB Express, 2020)
Pennisetum sinese Roxb (P. sinese) is an efficient and economic energy crop for its high productivity, and has been well studied in its application in phytoremediation and fodder production. However, little is known about how P. sinese plantation and fermented manures of P. sinese-feed livestock affect the composition of soil bacterial and fungal communities. In this study, 16S rRNA/ITS1 gene-based Illumina Miseq sequencing was employed to compare the bacterial and fungal community structure among soils that had been subjected to uncultivated control (CK), 2-year P. sinese plantation (P), and P. sinese plantation combined with the use of organic manures (P-OM) in a “P. sinese—breeding industry” ecological agriculture farm. The results found microbial communities were altered by P. sinese plantation and fertilization. The P. sinese plantation resulted in increased Actinobacteria and Planctomycetes abundance. Comparatively, significant increased abundance of Chloroflexi, Firmicutes, Nitrospirae, and Euryarchaeota, and genes related with nitrogen and carbon metabolic pathways based on PICRUSt prediction was observed in P-OM soil. Fungal compositions suggested a markedly increased abundance of Ascomycota in P soil. Potential organic matter decomposers Candida, Thermoascus, and Aspergillus were enriched in P soil, indicating the enhanced role of fungi in litter decomposition. Redundancy analysis suggested that soil properties (NH(4)(+)-N, total nitrogen, organic matter content, and soil water content) significantly correlated with the changes of microbial compositions (P < 0.05). These results highlight the divergence of microbial communities occurs during P. sinese-based plantation, implying functional diversification of soil ecosystem in P. sinese fields.